2013
DOI: 10.11118/actaun201361041005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial and economic crisis on SME's in Greece and Ireland

Abstract: The impact of financial and economic crisis influencing economic development in EU countries is analysed predominately on macroeconomic level. Major part of economic studies analyse the effect of crisis on both real and potential economic growth, unemployment, inflation and debt dynamic. However the effects of the crisis are visible also at microeconomic level. The economic results of businesses are significantly influenced by the negative macroeconomic development at both national and international level. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In a similar context, Vargo and Seville (2011) elucidated that economic and fiscal disruptions tend to create a financially constrained atmosphere for MSMEs. Even in the pre-Covid business environment, MSMEs were found prone to suffer through capital constraints as compared to large enterprises and corporate entities (Lacina and Vav rina, 2013). In empirical surveys, scholars have confirmed that the intensity of financial obstacles such as insufficient seed capital, inflated interest rates on external credit, elevated insurance costs, expensive carriage charges, training and recruitment costs, reduced sales turnover, high promotional costs, increased bad debts and heavy taxation liabilities threaten the regularity of MSMEs (Edmister, 1972;Pettit and Singer, 1985;Huang and Brown, 1999;Lownes-Jackson et al, 2003;Veskaisri et al, 2007;Naidu and Chand, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar context, Vargo and Seville (2011) elucidated that economic and fiscal disruptions tend to create a financially constrained atmosphere for MSMEs. Even in the pre-Covid business environment, MSMEs were found prone to suffer through capital constraints as compared to large enterprises and corporate entities (Lacina and Vav rina, 2013). In empirical surveys, scholars have confirmed that the intensity of financial obstacles such as insufficient seed capital, inflated interest rates on external credit, elevated insurance costs, expensive carriage charges, training and recruitment costs, reduced sales turnover, high promotional costs, increased bad debts and heavy taxation liabilities threaten the regularity of MSMEs (Edmister, 1972;Pettit and Singer, 1985;Huang and Brown, 1999;Lownes-Jackson et al, 2003;Veskaisri et al, 2007;Naidu and Chand, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The challenges faced by MSMEs have urged the government to take imperative action to aid the businesses to survive the challenges brought by the COVID-19 pandemic. Even in the pre-COVID business environment, MSMEs were found prone to suffer capital constraints as compared to large enterprises and corporate entities (Lacina & Vavřina, 2013). Thus, the Malaysian government has announced business supports and assistance in the form of the stimulus package to cushion the economic fallout and these packages can be categorized into two; Economic Stimulus Package Prihatin Rakyat (PRIHATIN) and PRIHATIN PLUS (Mustapa & Mohamad, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity alone is not enough to bring favorable results. Since they play a vital role in any national economy, this potential should be well developed and constantly nurtured by means of direct and indirect state support (Lacina and Vavřina, 2013).…”
Section: Introduction: Smes and Innovationsmentioning
confidence: 99%